Analysis of Stress Levels and Musculoskeletal Complaints in Pencak Silat Athletes (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
Stress is a non-specific response of the body to the demands that arise, which can be physiological and psychological reactions. Stress is a form of perception experienced by a person due to the gap between individual abilities and environmental demands that they experience. Psychological stress and high physical demands in training and competition are interrelated and often become factors that influence the performance and risk of musculoskeletal disorders in athletes. The musculoskeletal system consists of bones, joints, muscles, tendons, ligaments, and other supporting structures. The purpose of this study was to determine the level of stress and musculoskeletal complaints experienced by pencak silat athletes. This study used a cross-sectional method to describe the level of stress and musculoskeletal complaints in pencak silat athletes. Stress levels were measured using the Perceived Stress Scale (PSS) while musculoskeletal disorders were assessed using the Nordic Body Map. The research data showed that 75% of athletes experienced stress in the moderate category, while 25% were in the mild stress category. The results also revealed that 75% of athletes did not experience musculoskeletal complaints, while 25% needed attention in the future. Comprehensive monitoring of the physical and psychological condition of athletes is an important step for coaches and support teams to maintain consistent performance, prevent injuries, and ensure optimal athlete readiness.